PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA BADAN PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA PROPINSI SULAWESI TENGAH - Manitu, Erimas (Katalogis, 2017)
This study aimed to determine and analyze the influence of leadership style, both simultaneously and partially, on the employee performance of Central Sulawesi Board for Village Governance and Community Empowerment. The method used was survey method. The data used were primary and secondary data. This research was conducted at Central Sulawesi Board for Village Governance and Community Empowerment. Data were collected by means of questionnaires and observations of the 80 respondent employees of Central Sulawesi Board for Village Governance and Community Empowerment. The analytical tool used in this study was multiple linear regression analysis and the hypothesis testing used was F-test and T-test using SPSS for Windows 16.0. The result of multiple regression analysis showed that the leadership style had positive effects on the employee performance of Central Sulawesi Board for Village Governance and Community Empowerment. While the T-test result showed that partially the leadership style did not influence the employee performance and significantly influenced the employee work performance at Central Sulawesi Board for Village Governance and Community Empowerment.